Análisis cualitativo de enfoques de world class manufacturing para la generación de una herramienta de soporte aplicable a la industria de los alimentos (2017)
Abstract The World Class Manufacturing (WCM) methodology seeks new business development alternatives, encompasses principles and techniques for the effective management of production, quality, environment, safety, occupational health and personnel in an organization. Its implementation is a challenge for companies in Latin American industry, in particular in the food sector of Quito, who seek from the engineering to continue improving their processes to contribute to the development of the country. This research seeks from a qualitative analysis to clarify concepts of WCM and to collect tools and methods of improvement used in the food industry of Quito. To achieve this, a compilation of different WCM approaches has been documented in the industry, surveys and interviews with different professionals and managers located in the sector.